2015
DOI: 10.1080/23312009.2015.1112676
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental inhibitive properties of mild steel in HCl by ethanolic extract ofBoscia senegalensis

Abstract: The experimental aspect of the corrosion inhibition potentials of Boscia senegalensis was carried out using gravimetric and linear polarization techniques techniques as well as scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR), whereas the theoretical aspect was done by using the Density functional theory (DFT) calculations to performed and model the electronic structures of some extract constituents, including Physiosorptive interactions with the Fe surface. The analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…They conrmed the interaction of extract and mild steel by observing a change in the spectra aer immersing mild steel in extract-containing HCl solution. Awe et al 135 studied the inhibitive property of Boscia senegalensis on mild steel in HCl medium. The FTIR study revealed that C-N and C]O bonds were responsible for the inhibitor interaction with the surface of mild steel as those bonds were missing in the spectra.…”
Section: Conventional Characterization Techniquesmentioning
confidence: 99%
“…They conrmed the interaction of extract and mild steel by observing a change in the spectra aer immersing mild steel in extract-containing HCl solution. Awe et al 135 studied the inhibitive property of Boscia senegalensis on mild steel in HCl medium. The FTIR study revealed that C-N and C]O bonds were responsible for the inhibitor interaction with the surface of mild steel as those bonds were missing in the spectra.…”
Section: Conventional Characterization Techniquesmentioning
confidence: 99%
“…Molecular weight indicates the possible metal surface coverage by the inhibitor. The larger the molecular weight of an inhibitor, the greater the ionization energy because large molecule volume implies increased surface coverage [13]. Molecular weight indicates possible metal coverage.…”
Section: Global Reactivitymentioning
confidence: 99%
“…This configuration maximizes contact between the molecule and the metal surface. It has been reported that, the more negative the Eads of the inhibitor-metal surface, the better the adsorption of the inhibitor onto the metal surface and subsequently the higher the inhibition performance [32][33]. Based on the Eads values obtained, molecule B having more negative value of Eads is expected to perform better in inhibiting the corrosion of Al(1 1 0) in gas phase because of its molecular size and double bond on aromatic carbon atoms.…”
Section: Molecular Dynamic Simulationmentioning
confidence: 99%